Less cytotoxic phthalocyanine derivative promotes in vitro wound healing compared to chlorhexidine - Caique Andrade Santos; Adriano de Souza Pessoa; Fabiano Vieira Vilhena; Rodrigo Cardoso de Oliveira; Paulo Sérgio da Silva Santos; Carla Andreotti Damante; Mariana Schutzer Ragghianti Zangrando (Journal of Applied Biomaterials & Functional Materials)
The use of adjunct chemical substances in the early postoperative period of periodontal surgical procedures is recommended due to the potential risk of trauma in the operated area. Chlorhexidine digluconate mouthwash is widely used but can cause adverse effects. Phthalocyanine derivatives are being studied as an alternative, demonstrating good antimicrobial activity, especially in the self-activated form, which does not require additional light or chemicals. The objective of this study is to compare the cytotoxicity of different concentrations of a phthalocyanine (PHY) with chlorhexidine (CHX) and assess their influence on fibroblast cell migration. Different concentrations of CHX and PHY (0.0075%–0.12%) were evaluated using NIH 3T3 fibroblasts. Cell viability was assessed by the MTT and crystal violet (CV) assay; CHX and PHY (0.0075% and 0.12%) were also evaluated by in vitro wound healing assay. PHY was less cytotoxic compared to CHX, based on cell viability assays. PHY did not interfere with experimental healing, allowing cell migration similar to the positive control with both concentrations (PHY 0.0075% and 0.12%) and only 0.0075% CHX allowed cell migration. In a comparative analysis, PHY showed less cytotoxicity than CHX and PHY concentrations of 0.0075% and 0.015% was non-toxic even after 48 h of contact with the cells. This in vitro evaluation demonstrated that PHY was less cytotoxic to NIH 3T3 fibroblasts compared to CHX. Furthermore, the different concentrations of PHY did not interfere negatively in the healing of experimental wounds.